Anmeldelser - Woetmann Christoffersen, Peter (Danish Yearbook of Musicology, 2007)
Review of: Suzannah Clark and Elizabeth Eva Leach (eds.): Citation and Authority in Medieval and Renaissance Musical Culture. Learning from the Learned Studies in Medieval and Renaissance Music, 4. Woolbridge: The Boydell Press, 2005.